Ultrasonic Estimation of Pressure Dependent Non-Linearity Index in Liver - Nowicki, Andrzej; Tasinkiewicz, Jurij; Karwat, Piotr; Żołek, Norbert; Trots, Ihor; Tymkiewicz, Ryszard (Archives of Acoustics, 2026)
This study introduces a proof-of-concept methodology for evaluating pressure-dependent non-linear acoustic properties of liver tissue. The proposed non-linearity index (NLI) is derived from echo amplitudes obtained at two substantially different acoustic pressures. Unlike previous harmonic-based approaches, the method relies solely on the fundamental frequency band, allowing clinical implementation without additional system modifications. The image acquired for the lower pressure is then amplified to correct for the pressure difference between the beams. Next, the NLI is estimated as a ratio of local amplitudes of the amplified low-pressure image (ALPI) to the high-pressure image (HPI). In the case of nonlinear media some energy of the wave is transferred from the pulse fundamental frequency to higher harmonics, which affects mainly the HPI. With the harmonics being filtered out from the signal, the HPI amplitude becomes lower than the ALPI amplitude. As a result, the NLI becomes higher than 1 and increases with the non-linearity of the imaged tissue. The hydrophone measurements were compared to the simulation (k-Wave) of the ultrasonic field in water and vegetable oil. Next, we performed NLI imaging of healthy and fatty livers using SonixTouch (Ultrasonix) systems and two acoustic pressures of 390 kPa and 1590 kPa. Preliminary studies – imaging healthy and fatty livers using SonixTouch (Ultrasonix) systems were performed on the 4 livers of the authors of the article showed that for ‘healthy’ livers the NLI was below 1.1, while in one of the authors with previously diagnosed steatosis falling between score 1 and 2, the NLI locally exceeded 1.3.These results show that the obtained NLI values increase with the degree of steatosis, which agrees with theoretical expectations based on tissue B/A coefficients. The work emphasizes methodological feasibility and physical consistency rather than clinical validation, given the limited number of volunteers and ethical restrictions on patient recruitment.